Comprehensive analysis of the expression levels and prognostic values of PRDX family genes in glioma. (February 2022) - Szeliga, Monika
Abstract: Gliomas are a histologically and molecularly heterogeneous group of neoplasms accounting for 80% of malignant primary brain tumors. Growing evidence suggests that production of reactive oxygen species (ROS) is linked to glioma pathogenesis, although it is still unclear whether it is a cause or an effect of this process. Peroxiredoxins (PRDXs), a family of six antioxidant proteins, may promote or inhibit carcinogenesis, depending on the tumor type and stage. The current knowledge on their expression, regulation and functions in glioma is scarce. In this study, a comprehensive analysis of PRDXs expression in distinct glioma subtypes and non-tumor brain tissues was conducted using gene expression data from The Cancer Genome Atlas (TCGA), REpository for Molecular BRAin NeoplasiaDaTa (REMBRANDT), The Chinese Glioma Atlas (CGGA) and Gene Expression Omnibus (GEO) datasets. The association between gene expression and patient survival was investigated. DNA methylation, mutations, copy number alterations of deregulated PRDXs as well as the correlation between gene expression and tumor-infiltrating immune cells were assessed. The analysis revealed overexpression of PRDX1, PRDX4, and PRDX6 in most histological glioma types compared to the non-tumor tissues, while PRDX2, PRDX3 and PRDX5 expression remained unaltered. The expression of PRDX4 and PRDX6 was higher in mesenchymal than proneural and classical glioma subtypes. Moreover, lower expression of PRDX1, PRDX4 and PRDX6 was observed in tumors with a glioma CpG island methylator phenotype (G-CIMP) compared to non-G-CIMP tumors, as well as in isocitrate dehydrogenase (IDH) mutant and 1p/19q co-deleted gliomas compared to the wild-type counterparts. High expression of PRDX1, PRDX4 or PRDX6 correlated with poor survival of glioma patients. PRDX1 and PRDX6 displayed a positive correlation with different immune cell population in low grade gliomas and, to a lesser extent, in glioblastoma. PRDX1 expression exhibited negative correlation with DNA methylation. These results indicate that high expression of PRDX1, PRDX4 and PRDX6 is associated with poor outcome in gliomas. Highlights: PRDX1, PRDX4, PRDX6 are upregulated in most glioma subtypes compared to controls. Expression of PRDX2, PRDX3, PRDX5 remains unaltered in glioma compared to controls. High expression of PRDX1, PRDX4, PRDX6 correlates with poor patient survival. PRDX1 expression in gliomas negatively correlates with DNA methylation.